Modulation of structure and dynamics by disulfide bond formation in unfolded states - Silvers, Robert; Sziegat, Friederike; Tachibana, Hideki; Segawa, Shin-ichi; Whittaker, Sara; Günther, Ulrich L; Gabel, Frank; Huang, Jie-rong; Blackledge, Martin; Wirmer-Bartoschek, Julia; Schwalbe, Harald (Journal of the American Chemical Society, 2012)
During oxidative folding, the formation of disulfide bonds has profound effects on guiding the protein folding pathway. Until now, comparatively little is known about the changes in the conformational dynamics in folding intermediates of proteins that contain only a subset of their native disulfide bonds. In this comprehensive study, we probe the conformational landscape of non-native states of lysozyme containing a single native disulfide bond utilizing nuclear magnetic resonance (NMR) spectroscopy, small-angle X-ray scattering (SAXS), circular dichroism (CD) data, and modeling approaches. The impact on conformational dynamics varies widely depending on the loop size of the single disulfide variants and deviates significantly from random coil predictions for both NMR and SAXS data. From these experiments, we conclude that the introduction of single disulfides spanning a large portion of the polypeptide chain shifts the structure and dynamics of hydrophobic core residues of the protein so that these regions exhibit levels of order comparable to the native state on the nanosecond time scale.